Central obesity increases the risk of type 2 diabetes mellitus among urban adults - Pradono, Julianty; Kusumawardani, Nunik; Delima, Delima (Universa Medicina, 2015)
BackgroundIn Indonesia the number of persons with type 2 diabetes mellitus (T2DM) was 8.5 million in 2013, and is estimated to be 11.8 million in 2030. The aim of this study was to determine the major risk factors associated with T2DM prevalence in urban aged >15 years.MethodsAn observational study with cross-sectional design was used with the data from Riskesdas 2007 and 2013 on population aged >15 years. Total respondents were 294,352 (2007) and 368,281 (2013). Data were collected by trained personnel through interviews, blood pressure and anthropometry measurements, and blood glucose and lipid tests. Odds ratio (OR) was used to test the relationship between T2DM and a number of other variables. Multiple logistic regression analysis was obtained to determine the main risk factor associated with T2DM prevalence.ResultsType 2 diabetes mellitus prevalence increased from 2.3% (2007) to 2.5% (2013). T2DM tended to be increased in the younger age groups. Low education, middle-to-high economic status, less physical activity, smoking >200 cigarettes, and high risk blood lipid levels were strongly associated with T2DM prevalence. The main risk factors were inadequate physical activity (2007: OR 1.9;95% CI:1.16â2.98 and 2013: OR 2.44;95% CI: 1.57-3.78) and central obesity (2007: OR 1.8;95% CI:0.99â3.10, and 2013:OR 3.84; 95% CI: 2.49-5.93) after controlling for age, gender, employment and economic status.ConclusionsType 2 diabetes mellitus prevalence in the population aged >15 years increased within 5 years. Lack of physical activity and central obesity were the major risk factors of T2DM prevalence in urban adults.